2016
DOI: 10.20960/nh.101
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia de desnutrición en sujetos mayores de 65 años en la Comunidad de Madrid. Estudio DREAM + 65

Abstract: Cuerda C, Álvarez J, Ramos P, Abánades JC, García-de-Lorenzo A, Gil P, de-la-Cruz JJ. Prevalence of malnutrition in subjects over 65 years of age in the Community of Madrid. ResumenIntroducción: la desnutrición relacionada con la enfermedad (DRE) es un problema sociosanitario frecuente que afecta preferentemente a los mayores de 65 años, que aumenta la morbimortalidad y disminuye la calidad de vida.Objetivo: estudiar la prevalencia de DRE en mayores de 65 años en diferentes centros sociosanitarios del Servici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
1
4
0
1
Order By: Relevance
“…Analyzing the differences by gender, this study found a higher risk for women than men, consistent with the studies carried out by Cuerda et al (10) and Schilp et al (19) , and contrary to the study of Méndez et al (16) in which it was higher among men. These results could be attributed to the geographic environment or the time of data collection.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Analyzing the differences by gender, this study found a higher risk for women than men, consistent with the studies carried out by Cuerda et al (10) and Schilp et al (19) , and contrary to the study of Méndez et al (16) in which it was higher among men. These results could be attributed to the geographic environment or the time of data collection.…”
Section: Discussionsupporting
confidence: 91%
“…Based on international studies carried out with the elderly population living in their homes, the figures of risk of malnutrition vary from 15% to 40% (7)(8) ,whereas in studies conducted in Spain with non-institutionalized elderly people the estimate is nearly 20% (9)(10) . Frailty is defined as a situation in which the functional capacity of elderly people decreases, resulting in the risk of suffering adverse events and mortality, and is documented in several studies on states of malnutrition (9)(10)(11) . The knowledge on factors related to malnutrition will allow to plan specific activities for this population group, aimed at reducing frailty and improving quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Disease-related malnutrition (DRM) is a common social and health problem that mainly affects persons over the age of 65 years, increases their morbidity, and decreases their quality of life (1).…”
Section: Introductionmentioning
confidence: 99%
“…In Spain, data published over the past 10 years show that the prevalence of malnutrition in hospitalized patients ranges from 15.6 % to 86 % (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). The largest such study was the PREDyCES study, conducted in 2009, which involved 31 centers and included 1,707 patients, where nutritional status was assessed using the NRS-2002 (Nutritional Risk Screening 2002) tool within 48 hours of admission, which showed a DRM prevalence of 23.7 % in admitted patients (3).…”
Section: Introductionmentioning
confidence: 99%
“…Además, estudios llevados a cabo en pacientes mayores de 65 años muestran una prevalencia de desnutrición del 21,7% en hospitales, del 15,6% en residencias, del 2,2% en sujetos atendidos en atención primaria, y del 0,4% en los centros de mayores 26 .…”
Section: Funciones Específicasunclassified